Acceptability of Mental Health Facilities and De-addiction Centers in India. (April 2019) - Singh, Pahul Preet; Goel, Ishan; Mondal, Amit; Khan, Farooq Ali; Singh, Ashish Kumar; Dubey, Preeti; Chaudhary, Sushma; Reddy, P Venkata Anil Kumar; Rodrigues, Viola; Bassi, Vidhi; Ahuja, Karan; Shetty, Abhidith; et al.
Not much is known about disease prevalence, treatment outcomes, trained manpower, programs, and patients' awareness of diseases from South Asia, compared with the Western world. While other aspects are improving, the quantitative evaluation of awareness of diseases is lagging. Compared with other diseases, the situation for mental health disorders and addiction is worse. While no single study can fully quantify all aspects of awareness, a good starting point is to understand if increasing the number of mental health facilities is beneficial by understanding people's perception toward the likelihood of contracting various diseases, their preferred approach to treatment, and their perception of whether there are enough current facilities. We surveyed over 8000 families across several states of India and asked if they would treat a particular problem at home, visit a local healer, seek religious council, or go to a modern hospital for treatment. Our questions also included non-medical options to assess how likely people are to avoid trained medical help. We also asked people about their perceived likelihood of a family member ever suffering from (1) diarrhea, (2) high fever, (3) alcoholism, and (4) schizophrenia and other mental health problems. We reversed the order of diseases in our questions for a fraction of the population to evaluate the effect of order of questioning. Finally, we asked, if people feel they have enough local healers, religious places, general hospitals, de-addiction centers, and mental health facilities. Despite the taboo around mental health, many people claimed that their family members were unlikely to contract mental health or addiction problems, people recognized the severe paucity of mental health facilities and de-addiction centers. This raises hope for improving the mental health situation in India. We also found a significant relation between education levels and choices people make, underscoring the positive role education has in improving mental health.